O terreiro sagrado ibycarayba e a educação escolar indígena na aldeia Brejinho-PB - Lima, Genilson Silva de (2023)
The present study deals with the Terreiro Sagrado Ibycarayba and indigenous school education in the village of Brejinho-PB. The research focuses on the relationships between the spirituality of the sacred terreiro and the educational practices of the School and the application of the Cidadã Integral Indígena Antônio Sinésio da Silva. In it, we highlight the practices that students carry out to deepen their traditional knowledge within the terreiro and the great participation of the community of Aldeia Brejinho in the organization of the space of the terreiro. Indigenous school education seeks to follow what is provided for in the National Curricular Reference for Indigenous Schools, by recommending that didactic activities deal with the reality of each community. The general objective is to analyze the relations of the sacred terreiro, with the indigenous school education developed in Aldeia Brejinho and its interfaces with the Potiguara culture. It is based on authors such as: Barcellos (2014), Costa (2022), Palitot (2020; 2018), Santos e Silva (2021) among others. From a methodological point of view, the study has a qualitative approach with an ethnographic nature. First, we resorted to bibliographical research using participant observation, field diary, interviews with semi-structured questionnaires as research instruments, which were crucial for our reflections, since it was through them that we investigated the peculiar educational reality that involves the indigenous community. of Brejinho village and its interface with religiosity. The data collected show that it is of great value to use other spaces, in addition to the classroom, for the process of indigenous school education. The Sacred Terreiro works as one of those places, in which the specific ways of teaching the Potiguara culture can occur in a differentiated way.